Generation Z Narrative Strategy in Writing Short Stories: literary learning - Azzahra, Rizmada; Ariani, Dewi; Wijiati, Iva Ani; Asteria, Prima Vidya (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This study examines the narrative strategies used by Generation Z in writing short stories in the era of digital literacy. The research method used is a qualitative approach with descriptive analysis of the collection of short stories Warna Merdeka Kala Korona consisting of 47 short stories published by the Banyuwangi Literacy Community. Data were analyzed using Minderop’s (2011) storytelling strategy theory, which includes telling and showing techniques, as well as the influence of digital technology on narrative patterns. The results of the study show that changes in narrative structure in Generation Z short stories reflect adaptation to digital technology, with a dominance of non-linear plots, exploration of social themes, and active involvement of readers in interpreting the story. Generation Z shows a strong tendency to use an indirect storytelling style (showing), which develops characters and conflicts through actions, dialogues, and responses to problems without explicit narrative from the author. This study shows that technological developments have strengthened Generation Z’s preference for reflective and interactive storytelling. This study contributes to the study of digital literacy and opens up opportunities for further research related to cultural factors and individual preferences in shaping Generation Z’s storytelling strategies.